2008
DOI: 10.1038/eye.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

The rabbit as an animal model for post-natal vitreous matrix differentiation and degeneration

Abstract: Purpose This study evaluates whether rabbits are a suitable animal model to study post-natal vitreous differentiation and degeneration. Methods Human and rabbit eyes of various ages were studied by complementary anatomical techniques, light microscopy, and transmission electron microscopy. Results The global vitreous matrix organization is similar in human and rabbit eyes, lamellae are an important aspect thereof and show striking morphological changes with increasing age. In humans, liquefaction is more consp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…7) and that these changes were similar to those induced by trypsin (Figs. 5,8). Global effects of plasmin on the vitreous body outside the vitreoretinal interface have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…7) and that these changes were similar to those induced by trypsin (Figs. 5,8). Global effects of plasmin on the vitreous body outside the vitreoretinal interface have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 80%
“…To better understand the higher-level organization of the vitreous, alternative techniques have been used. For example, in aged human vitreous, injected colored dyes have highlighted fluid-filled lacunae, 8 and slit beam illumination has Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 indicated collapsed and tortuous fibers. [9][10][11] Noninvasive ultrasound 12,13 and magnetic resonance-based 14,15 techniques also have proved useful in assessing age-related vitreous liquefaction, but are currently limited by low spatial resolution.…”
mentioning
confidence: 99%
“…3, Table 2). Furthermore, Los (2008) showed that aging rabbit eye may be a good model for human vitreous liquefaction based on anatomical and histological analysis. Such a model may be a better approach than enzyme treatments to investigate the effect of the liquefying matrix or vitrectomy on vitreal drug elimination.…”
Section: Rabbit As An Animal Model In Intravitreal Pharmacokineticsmentioning
confidence: 99%
“…Despite this, some data obtained in rabbits can be useful to understand the mechanisms of ocular drug delivery such as the location and distribution of Galbumin™ in the eye after iontophoresis application and the pathway of Galbumin™ clearance after intravitreal injection. At the anatomical and histological levels, human and rabbit vitreous matrices are sufficiently similar to make the rabbit a promising animal model for the study of vitreous matrix differentiation and degeneration (Los, 2008). In summary, caution should be exercised to utilize the present results in ocular delivery development.…”
Section: Discussionmentioning
confidence: 99%